PERFECT DEMAND ILLUSION - Alexander Yu. Sulimov (Статистика и экономика)
The article is devoted to technique «Perfect demand illusion», which allows to strengthen the competitive advantageof retailers. Also in the paper spells out the golden rules of visual merchandising.The deﬁnition of the method «Demand illusion», formulated the conditions of its functioning, and is determined by the mainhypothesis of the existence of this method.Furthermore, given the deﬁnition of the «Perfect demand illusion», and describes its additional conditions. Also spells out the advantages of the «Perfect demandillusion», before the «Demand illusion».